Review on Nickel Aluminide based Bond Coat Properties and Oxidation Performance for Thermal Barrier Coating (TBC) Application - Kadir, NF.; Manap, A.; Satgunam, M.; Afandi, Nurfanizan Mohd (International Journal of Engineering and Technology, 2018)
Thermal Barrier Coating (TBC) as protective coatings are applied to maintain efficiency and prevent structural failures mainly in gas turbine system. This paper reviews on recent bond coating from Nickel aluminide bond coat with addition of Reactive Elements (RE). This paper also reviews the major concern in TBC with presence of different Reactive Element (RE) added in term of RE composition, properties and oxidation test performance. Recent studies are more focusing on few REs including Ce, Hf, La, Y and Zr based on oxidation property test results. The comparisons clearly show that ceramics addition are superior for bond coat mechanical and thermal properties improvement while RE addition such as Ce and Zr present excellent oxidation performance at 900Â°C and above.